Influence of residual pressure on the melting of a powder bed induced by a laser beam. (January 2022) - Annovazzi, Alicia; Dembinski, Lucas; Blanchet, Etienne; Vayre, Benjamin; Fenineche, Nouredine; Walrand, Gilles
Abstract: The laser beam melting (LBM) process is a powder-based additive manufacturing able to produce parts layer-by-layer in a hermetic chamber. Selection of the appropriate process parameters and fabrication conditions plays a fundamental role in the final properties. Investigating the interaction between the laser and the powder bed helps to understand the melt-pool behavior. In fact, even if additive manufacturing processes offer appreciable advantages, some processing parameters have to be studied to improve the properties of the products. The conventional LBM process is carried out in a chamber filled with an inert gas, at approximately atmospheric pressure. During the melting of a metal powder, gas can be caught in the liquid and may cause pores to form. This work investigates the effect of vacuum pressure in the chamber (up to 10 −2  mbar) on avoiding oxidation and improving the quality of the welding of stainless steel 316L. However, by modifying the residual pressure of the chamber, physical phenomena such as surface tension, Marangoni convection, and recoil pressure are amplified, creating more instabilities in the melt pool. This paper presents an initial analysis of the behavior of the powder under combinations of different residual pressures and laser speeds/powers. High-speed image acquisition brings to light the evolution of the spatters in vacuum compared to atmospheric pressure. Particle recovery coupled with Scanning Electron Microscopy (SEM) analyses shows the organization and morphologies of the ejections. Then, sectional views of single scan tracks are compared and related to the spattering. A considerable evolution in the results of the melting is found as one passes from atmospheric pressure to residual pressure. Hence, a powder pre-sintering solution is investigated in order to remedy the instabilities in vacuum and improve the process.